Evaluation of Electrocoagulation Process Efficiency in Laboratory Wastewater Treatment with Various Current Densities - Fatimura, Muhrinsyah; Tuty Emilia Agustina; Ian Kurniawan; Rully Masriatini; Nurlela; Reno Fitriyanti (Journal of Chemical Process Engineering, 2025)
Laboratory wastewater contains harmful compounds such as COD, TSS, heavy metals, and toxic compounds that require treatment before being discharged into the environment. Laboratory wastewater contains various hazardous pollutants that can pollute the environment if not managed properly. This study aims to evaluate the efficiency of the electrocoagulation process in the treatment of laboratory wastewater of the Chemical Engineering Study Program of PGRI University Palembang with variations in current density and reaction time. The experimental method was used by designing an electrocoagulation reactor using aluminum electrodes. The independent variables tested include current density (76.92 A/m², 87.17 A/m², and 102.56 A/m²) and reaction time of 15, 30, 60 minutes. Parameters analyzed included COD, TSS, TDS, pH, electrode consumption, and energy consumption. The results showed that the electrocoagulation process effectively reduced pollutant parameters; at a current density of 102.56 A/m² for 60 minutes, COD decreased to 63.5 mg/L, TSS to 23.52 mg/L, pH increased to 8, and turbidity reduced to 20.48 NTU. The specific energy consumption reached 18.2 kWh/m³ with an operational cost of Rp27,300/m³. Based on the analysis, the optimal current density for laboratory wastewater treatment is 102.56 A/m² with a reaction time of 60 minutes. Electrocoagulation technology is recommended as an efficient, effective, and environmentally friendly treatment method for laboratory wastewater in higher education institutions.